Maternal mortality related to pulmonary embolism in the United States, 2003-2020 - Farmakis, Ioannis T.; Barco, Stefano; Hobohm, Lukas; Braekkan, Sigrid K.; Connors, Jean M.; Giannakoulas, George; Hunt, Beverley J.; Keller, Karsten; Mavromanoli, Anna C.; Trinchero, Alice; Konstantinides, Stavros V.; Valerio, Luca (American journal of obstetrics and gynecology MFM, 2023)
BACKGROUND - Pulmonary embolism is a leading cause of maternal morbidity and mortality in Western countries. In the United States, pulmonary embolism-related mortality rates have plateaued in the general population after an initial decrease in the past 20 years. - OBJECTIVE - This study aimed to describe the changes in pulmonary embolism-related maternal mortality rates in the United States over the past 2 decades. - STUDY DESIGN - In this epidemiologic study of public vital registration data (death certificates encompassing underlying and contributing causes of death) from the Centers for Disease Control and Prevention Multiple Cause of Death database (2003-2020), we identified all maternal deaths with a pulmonary embolism code listed in any position of the death certificates. We investigated the changes in annual crude pulmonary embolism-related maternal mortality rates for the years 2003 to 2020, considering the effect of the introduction of the pregnancy checkbox in death certificates on the pulmonary embolism-related maternal mortality rates. - RESULTS - Overall, 735 pulmonary embolism-related maternal deaths out of 12,871 total maternal deaths (5.7%) were recorded between 2003 and 2020; the overall pulmonary embolism-related maternal mortality rate was 1.02 (95% confidence interval, 0.95-1.10) per 100,000 live births. The pulmonary embolism-related maternal mortality rate increased from 0.93 in 2003 to 1.96 in 2020; however, when accounting for the implementation of the pregnancy checkbox in the death certificates, the trends in pulmonary embolism-related maternal mortality were largely unchanged from 2003 to 2020. The crude pulmonary embolism-related maternal mortality rates differed across maternal age groups (overall 0.61, 1.09, and 3.83 maternal deaths per 100,000 live births for those aged ≤24, 25-39, and ≥40 years, respectively) and racial/ethnicity groups (2.89, 0.47, 0.77, and 0.63 maternal deaths per 100,000 live births for Black non-Hispanics, other non-Hispanics, White non-Hispanics, and Hispanics, respectively). - CONCLUSION - Maternal mortality rates related to pulmonary embolism did not decrease during the period from 2003 to 2020, as opposed to mortality rates related to pulmonary embolism in the general population. More research is required to assess whether improvement in venous thromboembolism prevention and pulmonary embolism diagnosis and management strategies might reduce death owing to pulmonary embolism in this vulnerable population.